Distinct cavemoviruses interact synergistically with sweet potato chlorotic stunt virus (genus Crinivirus) in cultivated sweet potato - Cuéllar, Wilmer Jose; Souza, J. de; Barrantes, Israel; Fuentes, S.; Kreuze, Jan F. (Microbiology Society, 2011)
Two serologically unrelated sweet potato viruses causing symptoms of vein clearing in the indicator plant Ipomoea setosa were isolated and their genomes have been sequenced. They are associated with symptomless infections in sweet potato but distinct vein-clearing symptoms and higher virus titres were observed when these viruses co-infected with sweet potato chlorotic stunt virus (SPCSV), a virus that is distributed worldwide and is a mediator of severe virus diseases in this crop. Molecular characterization and phylogenetic analysis revealed an overall nucleotide identity of 47.6 % and an arrangement of the movement protein and coat protein domains characteristic of members of the genus Cavemovirus, in the family Caulimoviridae. We detected both cavemoviruses in cultivated sweet potato from East Africa, Central America and the Caribbean islands, but not in samples from South America. One of the viruses characterized showed a similar genome organization as, and formed a phylogenetic sublineage with, tobacco vein clearing virus (TVCV), giving further support to the previously suggested separation of TVCV, and related viral sequences, into a new caulimovirid genus. Given their geographical distribution and previous reports of similar but yet unidentified viruses, sweet potato cavemoviruses may co-occur with SPCSV more often than previously thought and they could therefore contribute to the extensive yield losses and cultivar decline caused by mixed viral infections in sweet potato.